2017
DOI: 10.1002/app.45765
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of coating solution viscosity of hollow fiber‐supported polydimethylsiloxane membrane for CO2/H2 separation

Abstract: To optimize the CO 2 permeation and CO 2 /H 2 separation performance of hollow fiber-supported polydimethylsiloxane (PDMS) membranes, the effect of the viscosity of the PDMS coating solution on surface morphologies, thickness of PDMS layer, and solution intrusion into surface pores of hollow fiber supports was investigated. Increases in both stirring time and standing time could increase the viscosity of the PDMS solution. The PDMS layer thickness increased when the coating solution viscosity increased, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…[447][448][449][450][451]453,454,456,458,459,[463][464][465][466][467]472,473,475,[478][479][480]482,483,[484][485][486][487][488][489]496,497,[500][501][502]505,506,508,513,514,516,517,519,521,523,524,528,533,538,543]. One of the reasons for the low popularity of hydrophilic membranes is the low thermal and chemical stability of membranes, which in turn has an effect on the flux, demonstrated in Table…”
mentioning
confidence: 99%
“…[447][448][449][450][451]453,454,456,458,459,[463][464][465][466][467]472,473,475,[478][479][480]482,483,[484][485][486][487][488][489]496,497,[500][501][502]505,506,508,513,514,516,517,519,521,523,524,528,533,538,543]. One of the reasons for the low popularity of hydrophilic membranes is the low thermal and chemical stability of membranes, which in turn has an effect on the flux, demonstrated in Table…”
mentioning
confidence: 99%
“…However, the thickness of the nanolayer was not proportional to the concentration of the solution, and the layer thickens much faster than the increase of the concentration. It can be explained that the increase of the solid content in the solution leads to the advance of the solution viscosity, and a higher solution viscosity will make it easier to have more solution remained on the substrate and form a thicker film. , As a result, the thickness of the nanolayer increases significantly as the solution concentration increases.…”
Section: Resultsmentioning
confidence: 99%
“…It can be explained that the increase of the solid content in the solution leads to the advance of the solution viscosity, and a higher solution viscosity will make it easier to have more solution remained on the substrate and form a thicker film. 58,59 As a result, the thickness of the nanolayer increases significantly as the solution concentration increases. The properties of the plated copper film on the carrier copper foil are closely related to the thickness of the antiadhesion layer.…”
Section: Resultsmentioning
confidence: 99%
“…With a thicker coating layer, the gas permeance would normally decrease. 28,29 Longer holding time in coating solution also allows more intrusion of PDMS into the pores subsequently increasing the layer thickness as suggested by Hu et al 18 It should be noted that the holding time should not be too long, exceeding the gelation time of PDMS coating solution. Interestingly, both gases uphold the same permeance at 200 s and 900 s, which could be a sign that coating is present inconsistently.…”
Section: Machine Dip-coating -Influence Of Membrane Holding Timementioning
confidence: 95%
“…17 Not to mention, large surface pore could also limit the amount of PDMS solution that can adhere to the membrane's surface. 18 Nevertheless, as the solution becomes glutinous after 15 min, this suggested that crosslinking of PDMS is occurring and transfixed on the membrane's surface.…”
Section: Characterisation Of Manually Dip-coated Pes Hollow Fibre Membranementioning
confidence: 99%